Distribution of grape seed flavanols and their metabolites in pregnant rats and their fetuses. Issue 10 (3rd June 2013) - Arola‐Arnal, Anna; Oms‐Oliu, Gemma; Crescenti, Anna; del Bas, Josep Maria; Ras, Maria Rosa; Arola, Lluís; Caimari, Antoni
<x xml:space="preserve">Abstract</x> Scope Polyphenols have been demonstrated to provide health benefits affecting cellular and physiological processes. This study aims to evaluate the bioavailability and distribution of grape seed flavanol compounds during pregnancy and whether fetuses could be exposed to these compounds. Methods and results The distribution of flavanols and their metabolites in rat plasma, liver, white adipose tissue, brain, amniotic fluid, placenta, and fetuses after 1 and 2 h of an acute intake of a grape seed proanthocyanidin extract was examined by LC‐ESI‐TOF/MS. Flavanols and their metabolites were widely distributed in both pregnant and nonpregnant rat plasma and tissues. In liver, the conjugated forms of flavanols were less available in pregnant than nonpregnant rats. Flavanol metabolites were abundant in maternal placenta but detected at low levels in fetuses and amniotic fluid. Conclusion Flavanol metabolization appears to be less active in the liver during pregnancy. Moreover, data indicated that transport across the placenta is not efficient and for flavanols and their metabolites, the placenta seems to act as a barrier. However, these compounds target the fetus and are excreted in the amniotic fluid.